Postoperative pancreatic fistulas after pancreaticoduodenectomy for malignancy: A Northeast Indian tertiary cancer center study. Issue 9 (3rd August 2021) - Purkayastha, Joydeep; Bannoth, Srinivas; Talukdar, Abhijit; Borthakur, Bibhuti Bhusan; Kalita, Deepjyoti; Das, Gaurav; Kamalasanan, Kiran
Abstract: Background and Aim: Postoperative pancreatic fistula (POPF) is an important cause of major morbidity and mortality after pancreaticoduodenectomy. We intend to estimate the incidence and study the risk factors and outcomes of patients who developed this dreaded complication. Methods: This is a retrospective observational study. We included all patients who underwent pancreaticoduodenectomy at a specialized surgical unit of a single tertiary care cancer center in Northeast India. The period of study was from 23 April 2012 to 27 December 2019. The 2016 update on the definition of POPF by the International Study Group for Pancreatic Fistula was used to define the complication. Chi‐square test and Fischer's exact test were applied to categorical variables. t ‐test was used to quantify mean difference among continuous variables. P value <0.05 was considered statistically significant at 95% confidence interval. Results: A total of 59 patients underwent pancreaticoduodenectomy during the study period with almost equal distribution among males and females (29 and 30 patients respectively). The mean age of the patients was 54.0 years (range 20–72). Grade A, B, and C pancreatic fistulas were seen in five (8.5%), three (5.1%), and two (3.4%) patients, respectively. Preoperative hyperbilirubinemia, pancreatic duct size ≤3 mm, hypoalbuminemia, preoperative biliary decompression, and prolonged duration of surgery were identified as risk factors for POPF. POPF also resulted in increased 90‐day mortality (20%). Conclusion: POPF remains a potentially life‐threatening complication of pancreaticoduodenectomies. The knowledge and management of modifiable risk factors for this condition may help in mitigating this problem. Abstract : Postoperative pancreatic fistula remains a potentially life‐threatening complication of pancreaticoduodenectomies. Preoperative hyperbilirubinemia, pancreatic duct size less than or equal to 3 mm, hypoalbuminemia, preoperative biliary decompression, and prolonged duration of surgery were identified as risk factors for POPF. POPF also resulted in increased 90‐day mortality (20%).The knowledge and management of modifiable risk factors for this condition may help in mitigating this problem.